Russian translation of the novel "Wounds of Armenia" by Khachatur Abovyan - Шатирян, Асмик (Bulletin of Yerevan University H: Russian Philology, 2021)
The present article analyses the Russian translation of Kh. Abovian’s novel “Wounds of Armenia” carried out by S.Shervinskiy. This first novel in the modern Armenian literature has been considered as untranslatable for a long time due to the variety of style and stylistic layers presented in it. The article includes the interpretation findings used by S. Shervinski while recreating the national flavor, as well as the stylistic «polyphony» inherent in the novel. Particular attention is paid to the translation methods of the Armenian stable constructions, phraseological units, proverbs and other realia into Russian.